ATF - An end-to-end testing framework: experience report - Campos Junior, Heleno de Souza; Legey, Bruna Guerreiro Becker; Neves, Vânia de Oliveira; Blaschek, José Roberto de Souza (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2023: Anais do VIII Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2023)
Software products nowadays are becoming increasingly complex, containing modules directed for different devices, such as mobile and web. To maintain the quality of these products, development companies may adopt software testing techniques, such as end-to-end functional adequacy tests. However, a challenge arises when these companies serve diverse clients employing various technologies, requiring their developers and testers to possess knowledge across all these technologies. In this paper, we report our experience using the Automated Testing Framework (ATF), which makes the development of end-to-end functional adequacy tests easier for various types of devices in a standardized and organized manner. We also discuss its use on projects from two real clients presenting productivity data and feedback collected from the testers. Based on their feedback, we present the challenges they face and how we intend to tackle them.